HUBUNGAN MOTIVASI BELAJAR DENGAN KEMANDIRIAN BELAJAR SISWA SMPN 6 GARUT - Nurul Fauziah; Teti Sobari; Ecep Supriatna (FOKUS (Kajian Bimbingan & Konseling dalam Pendidikan), 2021)
The purpose of this research is to study whether there is a relationship between learning independence and motivation to learn in class VIII students of SMPN 6 Garut. The population in this study were eighth grade students of SMPN 6 Garut. The sampling technique uses purposive sampling technique so that research samples are obtained as many as 56 people. The research method uses quantitative correlational design with product estimation data analysis techniques based on learning motivation questionnaire data and student learning independence. Analysis of the data received with the application of spss 22 obtained significant research results between learning independence and learning motivation of grade VII students of SMPN 6 Garut with a comparison value of 0.822 in the category of very strong positive relationships. Hoping to learn while improving the learning of learners will increase.Keywords: : Learning motivation, learning independence